2018
DOI: 10.1080/21691401.2018.1522321
|View full text |Cite
|
Sign up to set email alerts
|

Immobilization of horseradish peroxidase on PMMA nanofibers incorporated with nanodiamond

Abstract: In the present study, nanodiamond (ND) was blended with polymethyl methacrylate (PMMA) and then electrospun into nanofibers (nfPMMA-ND) for the immobilization of horseradish peroxidase (HRP). The maximum immobilization efficiency of HRP (96%) was detected at 10% ND and pH 7.0. ATR-FTIR, SEM and TEM were used to characterize the immobilized enzyme. The immobilized enzyme retained 60% of its initial activity after ten reuses. The pH was shifted from 7.0 for soluble HRP to 7.5 for the immobilized enzyme. The solu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(14 citation statements)
references
References 42 publications
(54 reference statements)
0
14
0
Order By: Relevance
“…Enzyme is a kind of powerful biocatalyst evolved from nature. The vigorous development of biotechnology represented by enzyme catalysis has brought new opportunities for the sustainable development of the chemical industry. , As a highly efficient biocatalyst, natural enzymes have excellent specificity of the substrate, selectivity, and eco-friendly reaction conditions, imposing important impacts on biocompatibility, biodegradability, and renewability. , Although the stability of enzymes has been improved through protein engineering, the sensibility of enzymes leads to the lack of catalytic activity under extreme conditions. , In addition, a large amount of free enzymes cannot be recovered after the reaction, which remains a major difficulty in industrial production. , Hence, immobilized enzymes have been confirmed to be a useful strategy to improve the activity, stability, and selectivity of enzymes to achieve wider applications in the biochemical and medical industries. …”
Section: Introductionmentioning
confidence: 99%
“…Enzyme is a kind of powerful biocatalyst evolved from nature. The vigorous development of biotechnology represented by enzyme catalysis has brought new opportunities for the sustainable development of the chemical industry. , As a highly efficient biocatalyst, natural enzymes have excellent specificity of the substrate, selectivity, and eco-friendly reaction conditions, imposing important impacts on biocompatibility, biodegradability, and renewability. , Although the stability of enzymes has been improved through protein engineering, the sensibility of enzymes leads to the lack of catalytic activity under extreme conditions. , In addition, a large amount of free enzymes cannot be recovered after the reaction, which remains a major difficulty in industrial production. , Hence, immobilized enzymes have been confirmed to be a useful strategy to improve the activity, stability, and selectivity of enzymes to achieve wider applications in the biochemical and medical industries. …”
Section: Introductionmentioning
confidence: 99%
“…As observed, the highest removal efficiency of estrogen was noted at 32.4 • C, 39.4 • C, and 49.9 • C for free HRP, HRP immobilized onto PAA/PVA nanofibers, and HRP immobilized onto nanofibers with Fe 3 O 4 , respectively. Furthermore, it was observed that the removal of estrogen by immobilized biomolecules was significantly higher than after the process using free HRP at the entire investigated temperature range, which could be explained by the fact that support materials protect HRP against high-temperature-induced deactivation [56]. Surprisingly, in our research, the most suitable temperature for the most effective EE2 removal has been determined as 25 • C. In these conditions, the following three biocatalytic systems allowed us to remove 100% of EE2 from aqueous solutions: (i) nanoSiO 2 (HRP)-pure chitin, (ii) pure nanoSiO 2 -chitin(HRP), (iii) nanoSiO 2 (HRP)-chitin(HRP).…”
Section: Ee2 Removal Studymentioning
confidence: 93%
“…Many techniques have been utilized to immobilize and enhance the efficacy of enzyme by nanotechnology [57][58][59].…”
Section: Peroxidasesmentioning
confidence: 99%